Genealogical Inheritance Model of Javanese Coastal Batik: a Double Case Study on Batik-Making Families in Lasem and Tuban - RIZKYHIMAWAN, ADHYTIA; Eko Sugiarto; Wandah Wibawanto (Universitas Negeri Semarang, 2024)
Coastal Batik is a traditional artistic expression that thrives in the coastal areas of Indonesia, known for its beauty and resilience of character. The aims of this research are: (1) to examine and describe the special characteristics of Pesisir Batik work produced by batik-making families in Lasem and Tuban; (2) to analyze how various social, economic, and cultural aspects influence the practice of batik in families in Lasem and Tuban; and (3) to investigate the model or pattern of inheritance of batik skills and the Coastal Batik tradition in batik-making families in Lasem and Tuban. This research uses qualitative approach with a multiple case study research design and an art anthropology approach. Research data were collected using three techniques: observation, interviews, and documentation studies. Data analysis employs interactive analysis according to Milles & Huberman's view, which includes data reduction, data presentation, and drawing conclusions. Based on the results of this research, in the family realm, the inheritance process can be achieved through three methods: (1) conditioning, (2) imitation or modeling, and (3) internalization or learning to cope. This research reveals the complexity of the inheritance of cultural traditions. Cultural, social, and economic factors play a significant role in shaping batik practices in both regions. It also highlights how batik-making families strive to maintain their traditional heritage while adapting to changing times. The implications of this research extend to a deeper understanding of cultural preservation efforts in an ever-changing context, providing valuable insights for cultural preservation in Indonesia.